Evidence for excitonic condensation and superfluidity in black phosphorus - Jiadong Mei; Yue Wang; Ruixiang Fei; Junzhuan Wang; Xuetao Gan; Bo Liu; Xiaomu Wang (Nature Communications)
Abstract Excitonic condensation refers to the spontaneous formation of correlated electron-hole pairs. These collective states, also known as excitonic insulator, are expected to lead to intriguing many-body physics such as Bose-Einstein-condensates and Bardeen-Cooper-Schrieffer crossover. While the occurrence of excitonic insulator has been confirmed by measuring charge gaps, related macro-quantum phenomenon are less often observed. Here we report the signature of exciton insulator and its superfluidity in dual-gate few layer black phosphorus. Using Fourier transform infrared photo-current spectroscopy, we characterize the behavior of electron-hole pairs in black phosphorus. When shrinking the bandgap of photo-excited black phosphorus by electric displacement, we observe excitonic insulator formation featured by a sharp change of infrared photo-current spectrum and charge compressibility. This condensation presents a Bardeen-Cooper-Schrieffer -like temperature dependence with a critical temperature of ~17 K. We observe that the intrinsic black phosphorus photocurrent simultaneously vanishes with the formation of excitonic condensation. This vanished photocurrent is resilient against reasonable in-plane electric fields, indicating robust electron-hole pair binding state and providing evidence for the potential superfluidity of the exciton bosons. Our work not only reveals the exotic quantum phases and unusual orderings in excitonic insulator, but also provides a perspective for the study of composite Fermions.